A systematic review of direct oral anticoagulants for thromboprophylaxis in multiple myeloma - Cătălina Codreanu; Tessa Elling; Nic J.G. M. Veeger; Wilfried W.H. Roeloffzen; Karina Meijer (Research and Practice in Thrombosis and Haemostasis)
Multiple myeloma (MM) is associated with increased venous thromboembolism (VTE) risk. Current guidelines recommend aspirin or low-molecular-weight heparin for thromboprophylaxis depending on VTE risk. Nevertheless, VTE risks remain high: a recent meta-analysis reported an incidence of 6.2% during the entire MM course. Direct oral anticoagulants (DOACs) showed promising results in other malignancies. This systematic review provides an overview of evidence on DOAC thromboprophylaxis in MM. PubMed and Embase were searched up to November 21, 2023, for studies evaluating MM and DOAC thromboprophylaxis (PROSPERO: CRD42022376152). Two authors independently screened titles, abstracts, and texts, assessed bias using a modified version of the Newcastle Ottawa Scale and certainty of evidence with the Grading of Recommendations Assessment, Development and Evaluation approach, and performed data extraction and analysis. Seven articles comprising 416 patients with DOAC thromboprophylaxis were included, primarily involving newly diagnosed patients with MM (56.3%) receiving lenalidomide-based regimens (69.1%). Overall Newcastle Ottawa Scale study quality was moderate. Four studies reported follow-up duration ranging from 90 days after induction to 7 months. VTE proportions ranged from 0% to 23.5%, with 4 studies reporting 0%. The proportions of minor, clinically relevant nonmajor, and major bleeding ranged from 0% to 18.2%, 0% to 7.7%, and 0% to 4.5%, respectively. Arterial thrombosis proportions ranged from 0% to 2.9%. Only 2 studies reported on mortality (2% and 7.1%). Overall Grading of Recommendations Assessment, Development and Evaluation certainty of evidence was very low for all outcomes. Current evidence regarding routine DOACs in MM is insufficient, warranting further research to establish the DOAC thromboprophylaxis risk-to-benefit ratio in MM.